Fe-Co-Ni-Cu-Zn high-entropy sensing material, preparation method, sensing electrode and application thereof

The Fe-Co-Ni-Cu-Zn high-entropy sensing material is prepared by electrochemical deposition method, which solves the problems of low accuracy and poor stability of existing detection materials, and realizes the detection of various biomolecules with high accuracy and good stability. .

CN119332319APending Publication Date: 2025-01-21SHENZHEN INST OF ADVANCED TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310906166.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In electrochemical sensing, existing detection materials have problems such as low detection accuracy, poor stability and low zero degree sensitivity, and it is difficult to detect glucose and urea at the same time.

Method used

Fe-Co-Ni-Cu-Zn high-entropy sensing materials are prepared using electrochemical deposition methods. By configuring the electroplating solution and adjusting the concentration and PH value of the electrolyte, the elemental composition and organizational morphology of the high-entropy alloy are controlled to improve detection. Material properties.

Benefits of technology

It achieves high-precision and stable detection, can detect urea and glucose simultaneously, and has high zero sensitivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332319A_ABST
    Figure CN119332319A_ABST
Patent Text Reader

Abstract

According to the preparation method of the Fe-Co-Ni-Cu-Zn high-entropy sensing material, the Fe-Co-Ni-Cu-Zn high-entropy sensing material is obtained by preparing an electroplating solution, adjusting the concentration and the PH value of the electrolyte and conducting sensitive material preparation on Fe, Co, Ni, Cu and Zn elements through an electrochemical method, and the preparation method is easy and convenient to operate, low in cost and energy consumption and suitable for industrial production. The elemental composition, the structure morphology, the performance and the like of the high-entropy alloy can be easily controlled by changing deposition parameters (time, temperature and the like) through electrochemical deposition; the Fe-Co-Ni-Cu-Zn high-entropy sensing material prepared by the invention can be used as a sensing electrode to test urea and glucose solutions with different concentrations, and is high in detection precision, good in stability and high in zero-degree sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of material detection technology, and in particular to a method for preparing a Fe-Co-Ni-Cu-Zn high entropy sensing material, a Fe-Co-Ni-Cu-Zn high entropy sensing material and applications thereof. Background Art

[0002] Detection materials are the key to electrochemical sensing. Current detection materials have the problems of low detection accuracy, poor stability, and low zero-degree sensitivity. In addition, it is difficult for the same electrode material to simultaneously detect glucose and urea. There is an urgent need to develop new detection materials for biochemical sensors.

[0003] High entropy alloy is a solid solution alloy material composed of five or more metal elements in equiatomic or non-equiatomic ratios. Due to the difference in its structure from traditional alloys, high entropy alloys have the following unique effects: high entropy effect, lattice distortion effect, hysteresis diffusion effect and "cocktail effect", which also enables them to obtain many attractive properties, such as mechanical properties, corrosion resistance, unique electromagnetic properties, etc.

[0004] At present, the preparation methods of high entropy alloys mainly include physical methods such as arc induction melting, thermal spraying, laser cladding, and mechanical die casting. The existing methods have great difficulty in experimental operation, complex processing routes, and limited control effects. The use of electrochemical deposition for the regulation of high entropy alloys is a low-cost, simple-to-operate preparation method. Compared with other control methods, it can regulate the element ratio and chemical composition of HEA on substrates with complex geometric shapes. It is easy to operate, has low requirements for the processing environment, does not require complex equipment and expensive raw materials, and provides great convenience for engineering applications. In addition, electrochemical deposition can easily control the element composition, organizational morphology, and properties of high entropy alloys by changing deposition parameters (time, temperature, etc.). Therefore, it is possible to regulate the organization and properties of high entropy alloys by adjusting the electrochemical deposition parameters. Summary of the invention

[0005] In view of this, it is necessary to provide a method for preparing a Fe-Co-Ni-Cu-Zn high entropy sensing material, a Fe-Co-Ni-Cu-Zn high entropy sensing material, a sensing material and its application which are easy to operate, low cost, low energy consumption and can be controlled in order to address the defects in the prior art.

[0006] To solve the above problems, this application adopts the following technical solutions:

[0007] One of the purposes of this application is to provide a method for preparing a Fe-Co-Ni-Cu-Zn high entropy sensing material, comprising the following steps:

[0008] Prepare an electrolyte, wherein the electroplating solution includes the following components: soluble iron salt, cobalt salt, nickel salt, copper salt, zinc salt, complexing agent, buffer, reducing agent and additional salt;

[0009] Adjusting the concentration and pH value of the electrolyte;

[0010] The adjusted electrolyte is electroplated to obtain the Fe-Co-Ni-Cu-Zn high entropy sensing material.

[0011] In some of the embodiments, in the step of configuring the electrolyte, the soluble iron salt includes ferrous sulfate, the cobalt salt includes cobalt sulfate, the nickel salt includes nickel sulfate, the copper salt includes copper sulfate, and the zinc salt includes zinc sulfate; the chelating agent includes but is not limited to citric acid or trisodium citrate; the buffer includes but is not limited to boric acid; the reducing agent includes but is not limited to sodium hypophosphite; and the additional salt includes but is not limited to potassium chloride.

[0012] In some embodiments, the step of preparing the electrolyte specifically includes the following steps:

[0013] First, deionized water is heated and maintained at a temperature of 20° C.-90° C., and then the complexing agent, the buffer, and the additional salt are added in sequence and stirred until dissolved, and then the soluble iron salt, the cobalt salt, the nickel salt, the copper salt, the zinc salt, and the reducing agent are added and stirred until dissolved, and after aging for 0.2-8 hours, the electrolyte is obtained.

[0014] In some embodiments, the step of adjusting the concentration and pH value of the electrolyte specifically includes the following steps:

[0015] A strong acid solution is added to the electrolyte, and the concentration and pH value of the electrolyte are adjusted to make the pH value of the electrolyte 7.0-8.5.

[0016] In some of the embodiments, the contents of the components of the electroplating solution are as follows: 5.0-200.0 g / L ferrous sulfate, 5.0-180.0 g / L cobalt sulfate, 5.0-150 g / L nickel sulfate, 5.0-100.0 g / L potassium chloride, 0.1-50.0 g / L copper sulfate, 0.2-60.0 g / L zinc sulfate, 1.0-50.0 g / L trisodium citrate, 0.1-20 g / L sodium hypophosphite, 10.0-200.0 g / L citric acid, and 2.0-80.0 g / L boric acid.

[0017] In some embodiments, the strong acid solution includes but is not limited to sulfuric acid solution, hydrochloric acid solution or nitric acid solution, and the concentration of the sulfuric acid solution is 0.1-6 mol / L.

[0018] In some embodiments, the step of electroplating the adjusted electrolyte to obtain the Fe-Co-Ni-Cu-Zn high entropy sensing material specifically includes the following steps:

[0019] The Fe-Co-Ni-Cu-Zn high entropy sensing material is obtained by using an electrode rod as an anode and a conductive substrate as a cathode and performing electroplating at a constant potential, wherein the electrodeposition potential ranges from -3.0 to 3.0 V, the deposition temperature is 30 to 80° C., and the deposition time ranges from 0.1 to 50 min during the electroplating process.

[0020] In some embodiments, the conductive substrate includes but is not limited to titanium, copper, and silver; the electrode rod includes but is not limited to a millstone rod, lead, titanium, and platinum.

[0021] In some of the embodiments, the conductive substrate further includes a pretreatment step before use, and the pretreatment includes first polishing the conductive substrate with sandpaper, then ultrasonically treating it for 5-20 minutes, then soaking it in a 0.5-2 mol / L sulfuric acid solution for 0.5-8 hours, and then rinsing it with pure water and ethanol in turn, and drying it.

[0022] In some of the embodiments, the ratio of each metal element in the Fe-Co-Ni-Cu-Zn high entropy sensing material is between 1% and 50%.

[0023] The second purpose of the present application is to provide a Fe-Co-Ni-Cu-Zn high entropy sensing material, which is prepared by the preparation method of the Fe-Co-Ni-Cu-Zn high entropy sensing material.

[0024] The third object of the present application is to provide a sensing electrode comprising the Fe-Co-Ni-Cu-Zn high entropy sensing material.

[0025] The fourth purpose of the present application is to provide an application of the sensing electrode in detecting the concentrations of urea and glucose.

[0026] In some of the embodiments, the detection concentration range of urea is 0.2-1.4 mM, and the detection concentration range of glucose is 0.1-0.5 mM.

[0027] This application adopts the above technical solution, and its beneficial effects are as follows:

[0028] The invention provides a preparation method of a Fe-Co-Ni-Cu-Zn high entropy sensing material. The method comprises the following steps: preparing a plating solution, adjusting the concentration and pH value of the electrolyte, and preparing sensitive materials of Fe, Co, Ni, Cu and Zn elements by an electrochemical method to obtain the Fe-Co-Ni-Cu-Zn high entropy sensing material. The preparation method is simple to operate, and has low cost and energy consumption. The element composition, microstructure and performance of the high entropy alloy can be easily controlled by changing deposition parameters (time, temperature, etc.) through electrochemical deposition. The Fe-Co-Ni-Cu-Zn high entropy sensing material prepared by the invention can be used as a sensing electrode to test urea and glucose solutions of different concentrations, and has high detection accuracy, good stability and high zero-degree sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0030] Figure 1 This is a flow chart of the steps of the method for preparing the Fe-Co-Ni-Cu-Zn high entropy sensing material provided in an embodiment of the present application.

[0031] Figure 2 This is the SEM and element distribution diagram of the high entropy electrode material provided in Example 1 of the present application.

[0032] Figure 3 The electrochemical scanning curves under different common sugar concentrations provided in Example 5 of the present application.

[0033] Figure 4 The electrochemical scanning curves under different common sugar concentrations provided in Example 6 of the present application. DETAILED DESCRIPTION

[0034] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.

[0035] In the description of the present application, it should be understood that the terms "upper", "lower", "horizontal", "inside", "outside", etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0036] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0037] In order to make the objectives, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0038] See also Figure 1 The step flow chart of the preparation method of the Fe-Co-Ni-Cu-Zn high entropy sensing material provided in the present application includes the following steps S110 to S130, and the implementation method of each step is described in detail below.

[0039] Step S110: preparing an electrolyte, wherein the electroplating solution includes the following components: soluble iron salt, cobalt salt, nickel salt, copper salt, zinc salt, complexing agent, buffer, reducing agent and additional salt.

[0040] In this embodiment, the step of preparing the electrolyte specifically includes the following steps:

[0041] First, deionized water is heated and maintained at a temperature of 20° C.-90° C., and then the complexing agent, the buffer, and the additional salt are added in sequence and stirred until dissolved, and then the soluble iron salt, the cobalt salt, the nickel salt, the copper salt, the zinc salt, and the reducing agent are added and stirred until dissolved, and after aging for 0.2-8 hours, the electrolyte is obtained.

[0042] In this embodiment, the soluble iron salt includes ferrous sulfate, the cobalt salt includes cobalt sulfate, the nickel salt includes nickel sulfate, the copper salt includes copper sulfate, and the zinc salt includes zinc sulfate; the chelating agent includes but is not limited to citric acid or trisodium citrate; the buffer includes but is not limited to boric acid; the reducing agent includes but is not limited to sodium hypophosphite; and the additional salt includes but is not limited to potassium chloride.

[0043] Furthermore, the contents of the components of the electroplating solution are as follows: 5.0-200.0 g / L ferrous sulfate, 5.0-180.0 g / L cobalt sulfate, 5.0-150 g / L nickel sulfate, 5.0-100.0 g / L potassium chloride, 0.1-50.0 g / L copper sulfate, 0.2-60.0 g / L zinc sulfate, 1.0-50.0 g / L trisodium citrate, 0.1-20 g / L sodium hypophosphite, 10.0-200.0 g / L citric acid, and 2.0-80.0 g / L boric acid.

[0044] Step S120: adjusting the concentration and pH value of the electrolyte.

[0045] In this embodiment, the step of adjusting the concentration and pH value of the electrolyte specifically includes the following steps: adding a strong acid solution to the electrolyte, adjusting the concentration and pH value of the electrolyte, and making the pH value of the electrolyte be 7.0-8.5.

[0046] Furthermore, the strong acid solution includes but is not limited to sulfuric acid solution, hydrochloric acid solution or nitric acid solution, and the concentration of the sulfuric acid solution is 0.1-6 mol / L.

[0047] It can be understood that by adding an appropriate amount of strong acid solution to the electroplating solution, the concentration and pH value of the electroplating solution can be adjusted to better meet the subsequent preparation requirements of Fe-Co-Ni-Cu-Zn high entropy sensing materials.

[0048] Step S130: electroplating the adjusted electrolyte to obtain the Fe-Co-Ni-Cu-Zn high entropy sensing material.

[0049] In this embodiment, the step of electroplating the adjusted electrolyte to obtain the Fe-Co-Ni-Cu-Zn high entropy sensing material specifically includes the following steps: using an electrode rod as an anode and a conductive substrate as a cathode, and performing electroplating at a constant potential to obtain the Fe-Co-Ni-Cu-Zn high entropy sensing material.

[0050] Furthermore, during the electroplating process, the electrodeposition potential ranges from -3.0 to 3.0 V, the deposition temperature ranges from 30 to 80° C., and the deposition time ranges from 0.1 to 50 min.

[0051] It can be understood that by changing the deposition parameters (time, temperature, etc.) through electrochemical deposition, the elemental composition, microstructure, and properties of high entropy alloys can be easily controlled. Therefore, the adjustment of electrochemical deposition parameters provides the possibility of regulating the microstructure and properties of high entropy alloys.

[0052] In this embodiment, the conductive substrate includes but is not limited to titanium, copper, and silver; the electrode rod includes but is not limited to a millstone rod, lead, titanium, and platinum.

[0053] Furthermore, the conductive substrate also includes a pretreatment step before use, and the pretreatment includes first polishing the conductive substrate with sandpaper, then ultrasonically treating it for 5-20 minutes, then soaking it in a 0.5-2 mol / L sulfuric acid solution for 0.5-8 hours, and then washing it with pure water and ethanol in turn, and drying it.

[0054] In this embodiment, the ratio of each metal element in the Fe-Co-Ni-Cu-Zn high entropy sensing material is between 1% and 50%.

[0055] The above embodiment of the present application provides a method for preparing a Fe-Co-Ni-Cu-Zn high entropy sensing material. By preparing an electroplating solution, adjusting the electrolyte concentration and pH value, and preparing sensitive materials for Fe, Co, Ni, Cu, and Zn elements by an electrochemical method, Fe-Co-Ni-Cu-Zn high entropy sensing material is obtained. The above preparation method is simple to operate, with low cost and energy consumption. By changing the deposition parameters (time, temperature, etc.) through electrochemical deposition, the elemental composition, organizational morphology, and performance of the high entropy alloy can be easily controlled.

[0056] The Fe-Co-Ni-Cu-Zn high entropy sensing material prepared in the present application can be used as a sensing electrode to test urea and glucose solutions of different concentrations.

[0057] In some of the embodiments, the detection concentration range of urea is 0.2-1.4 mM, and the detection concentration range of glucose is 0.1-0.5 mM.

[0058] The sensing electrode provided in the present application includes Fe-Co-Ni-Cu-Zn high entropy sensing material, which can simultaneously detect glucose and urea with high detection accuracy, good stability and high zero-degree sensitivity.

[0059] The above technical solution of the present application is described in detail below in conjunction with specific embodiments.

[0060] Example 1

[0061] Example 1 of the present application provides a preparation method of a Fe-Co-Ni-Cu-Zn high entropy sensing material, and the preparation method is as follows:

[0062] (1) First, deionized water is heated and maintained at a temperature of 20° C., and then citric acid, boric acid, and potassium chloride are added in sequence and stirred until dissolved, and then ferrous sulfate, cobalt sulfate, nickel sulfate, copper sulfate, zinc sulfate, and sodium hypophosphite are added and stirred until dissolved. After aging for 0.2 h, the electrolyte is obtained.

[0063] (2) Add 0.1 mol / L sulfuric acid solution to the electrolyte, and adjust the concentration and pH value of the electrolyte to 7.0. Among them: 5.0 g / L ferrous sulfate, 5.0 g / L cobalt sulfate, 5.0 g / L nickel sulfate, 5.0 g / L potassium chloride, 0.1 g / L copper sulfate, 0.2 g / L zinc sulfate, 0.1 g / L sodium hypophosphite, 10.0 g / L citric acid, and 2.0 g / L boric acid.

[0064] (3) A stone mill rod is used as an anode and titanium is used as a cathode, and a constant potential electroplating treatment is performed to obtain the Fe-Co-Ni-Cu-Zn high entropy sensing material, wherein the electrodeposition potential range during the electroplating process is -3.0 V, the deposition temperature is 30° C., and the deposition time range is 0.1 min.

[0065] See also Figure 2 , is the SEM image and element distribution diagram provided in Example 1.

[0066] Example 2

[0067] Example 2 of the present application provides a preparation method of a Fe-Co-Ni-Cu-Zn high entropy sensing material, and the preparation method is as follows:

[0068] (1) First, deionized water is heated and maintained at 90° C., and then trisodium citrate, boric acid, and potassium chloride are added in sequence and stirred until dissolved, and then ferrous sulfate, cobalt sulfate, nickel sulfate, copper sulfate, zinc sulfate, and sodium hypophosphite are added and stirred until dissolved. After aging for 8 hours, the electrolyte is obtained.

[0069] (2) Add 6 mol / L sulfuric acid solution to the electrolyte, and adjust the concentration and pH value of the electrolyte to 7.5. Among them: 200.0 g / L ferrous sulfate, 180.0 g / L cobalt sulfate, 150 g / L nickel sulfate, 100.0 g / L potassium chloride, 50.0 g / L copper sulfate, 60.0 g / L zinc sulfate, 1.0 g / L trisodium citrate, 20 g / L sodium hypophosphite, and 80.0 g / L boric acid.

[0070] (3) A stone mill rod is used as an anode and titanium is used as a cathode, and a constant potential electroplating treatment is performed to obtain the Fe-Co-Ni-Cu-Zn high entropy sensing material, wherein the electrodeposition potential range during the electroplating process is 3.0 V, the deposition temperature is 80° C., and the deposition time range is 50 min.

[0071] Example 3

[0072] Example 3 of the present application provides a preparation method of a Fe-Co-Ni-Cu-Zn high entropy sensing material, and the preparation method is as follows:

[0073] (1) First, deionized water is heated and maintained at a temperature of 50° C., and then trisodium citrate, boric acid, and potassium chloride are added in sequence and stirred until dissolved, and then ferrous sulfate, cobalt sulfate, nickel sulfate, copper sulfate, zinc sulfate, and sodium hypophosphite are added and stirred until dissolved. After aging for 4 hours, the electrolyte is obtained.

[0074] (2) Add 3 mol / L sulfuric acid solution to the electrolyte, and adjust the concentration and pH value of the electrolyte to 8.2. Among them: 50.0 g / L ferrous sulfate, 80.0 g / L cobalt sulfate, 100 g / L nickel sulfate, 50.0 g / L potassium chloride, 20.0 g / L copper sulfate, 30.0 g / L zinc sulfate, 20.0 g / L trisodium citrate, 10 g / L sodium hypophosphite, and 40.0 g / L boric acid.

[0075] (3) A stone mill rod is used as an anode and titanium is used as a cathode, and a constant potential electroplating treatment is performed to obtain the Fe-Co-Ni-Cu-Zn high entropy sensing material, wherein the electrodeposition potential range during the electroplating process is 3.0 V, the deposition temperature is 80° C., and the deposition time range is 50 min.

[0076] Example 4

[0077] Example 3 of the present application provides a preparation method of a Fe-Co-Ni-Cu-Zn high entropy sensing material, and the preparation method is as follows:

[0078] (1) First, deionized water is heated and maintained at a temperature of 30° C., and then citric acid, boric acid, and potassium chloride are added in sequence and stirred until dissolved, and then ferrous sulfate, cobalt sulfate, nickel sulfate, copper sulfate, zinc sulfate, and sodium hypophosphite are added and stirred until dissolved. After aging for 5 hours, the electrolyte is obtained.

[0079] (2) Add 3 mol / L sulfuric acid solution to the electrolyte, and adjust the concentration and pH value of the electrolyte to 8.5. Among them: 40.0 g / L ferrous sulfate, 30.0 g / L cobalt sulfate, 10 g / L nickel sulfate, 20.0 g / L potassium chloride, 10.0 g / L copper sulfate, 20.0 g / L zinc sulfate, 50.0 g / L citric acid, 8 g / L sodium hypophosphite, and 20.0 g / L boric acid.

[0080] (3) A stone mill rod is used as an anode and titanium is used as a cathode, and a constant potential electroplating treatment is performed to obtain the Fe-Co-Ni-Cu-Zn high entropy sensing material, wherein the electrodeposition potential range during the electroplating process is 2.0 V, the deposition temperature is 60° C., and the deposition time range is 30 min.

[0081] Table 1 shows the content of elements in Examples 1-4

[0082]

[0083]

[0084] Example 5

[0085] Potassium chloride was dissolved in 100 ml of deionized water to obtain a 0.1 M solution, and then different amounts of glucose were added to prepare a solution with a concentration of 0.2 to 1.4 μM.

[0086] The high entropy electrode material is deposited on the surface of the working electrode by the method of Example 1 to prepare a high entropy electrode.

[0087] The high entropy electrode and the prepared Au-HEA electrode were scanned at a scan rate of 50 mV / s and in a point range of 0.2 V to 0.8 V. The oxidation peak in the range was found in advance, and a linear relationship was fitted by linear fitting. Figure 3 The electrochemical scanning curves at different common sugar concentrations provided in Example 5.

[0088] Example 6

[0089] Potassium chloride was dissolved in 100 ml of deionized water to obtain a 0.1 M solution, and then different amounts of glucose were added to prepare a solution with a concentration of 0.1 to 0.5 μM.

[0090] The high entropy electrode material is deposited on the surface of the working electrode by the method of Example 3 to prepare a high entropy electrode.

[0091] The high entropy electrode and the prepared Au-HEA electrode were scanned at a scan rate of 50 mV / s and in a point range of -0.35 V to 0 V. The oxidation peak in the range was obtained in advance, and a linear relationship was fitted by linear fitting. Figure 4 The electrochemical scanning curves at different common sugar concentrations provided in Example 6.

[0092] It can be understood that the technical features of the above-described embodiments can be arbitrarily combined. In order to make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0093] The above are only preferred embodiments of the present application, and only specifically describe the technical principles of the present application. These descriptions are only for explaining the principles of the present application and cannot be interpreted as limiting the scope of protection of the present application in any way. Based on the explanation here, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application, and other specific implementation methods of the present application that can be associated with the technicians in this field without creative work, should be included in the scope of protection of the present application.

Claims

1. A method for preparing a Fe-Co-Ni-Cu-Zn high entropy sensing material, characterized in that: The steps include: Prepare an electrolyte, wherein the electroplating solution includes the following components: soluble iron salt, cobalt salt, nickel salt, copper salt, zinc salt, complexing agent, buffer, reducing agent and additional salt; Adjusting the concentration and pH value of the electrolyte; The adjusted electrolyte is electroplated to obtain the Fe-Co-Ni-Cu-Zn high entropy sensing material.

2. The method for preparing the Fe-Co-Ni-Cu-Zn high entropy sensing material according to claim 1, characterized in that: In the step of configuring the electrolyte, the soluble iron salt includes ferrous sulfate, the cobalt salt includes cobalt sulfate, the nickel salt includes nickel sulfate, the copper salt includes copper sulfate, and the zinc salt includes zinc sulfate; the complexing agent includes but is not limited to citric acid or trisodium citrate; the buffer includes but is not limited to boric acid; the reducing agent includes but is not limited to sodium hypophosphite; and the additional salt includes but is not limited to potassium chloride.

3. The method for preparing the Fe-Co-Ni-Cu-Zn high entropy sensing material according to claim 1 or 2, characterized in that: The steps of preparing the electrolyte specifically include the following steps: First, deionized water is heated and maintained at a temperature of 20° C.-90° C., and then the complexing agent, the buffer, and the additional salt are added in sequence and stirred until dissolved, and then the soluble iron salt, the cobalt salt, the nickel salt, the copper salt, the zinc salt, and the reducing agent are added and stirred until dissolved, and after aging for 0.2-8 hours, the electrolyte is obtained.

4. The method for preparing the Fe-Co-Ni-Cu-Zn high entropy sensing material according to claim 2, characterized in that: The step of adjusting the concentration and pH value of the electrolyte specifically includes the following steps: A strong acid solution is added to the electrolyte, and the concentration and pH value of the electrolyte are adjusted to make the pH value of the electrolyte 7.0-8.

5.

5. The method for preparing the Fe-Co-Ni-Cu-Zn high entropy sensing material according to claim 4, characterized in that: The components of the electroplating solution are as follows: 5.0-200.0 g / L of ferrous sulfate, 5.0-180.0 g / L of cobalt sulfate, 5.0-150 g / L of nickel sulfate, 5.0-100.0 g / L of potassium chloride, 0.1-50.0 g / L of copper sulfate, 0.2-60.0 g / L of zinc sulfate, 1.0-50.0 g / L of trisodium citrate, 0.1-20 g / L of sodium hypophosphite, 10.0-200.0 g / L of citric acid, and 2.0-80.0 g / L of boric acid.

6. The method for preparing the Fe-Co-Ni-Cu-Zn high entropy sensing material according to claim 5, characterized in that: The strong acid solution includes but is not limited to sulfuric acid solution, hydrochloric acid solution or nitric acid solution, and the concentration of the sulfuric acid solution is 0.1-6 mol / L.

7. The method for preparing the Fe-Co-Ni-Cu-Zn high entropy sensing material according to claim 1, characterized in that: The step of electroplating the adjusted electrolyte to obtain the Fe-Co-Ni-Cu-Zn high entropy sensing material specifically includes the following steps: The Fe-Co-Ni-Cu-Zn high entropy sensing material is obtained by using an electrode rod as an anode and a conductive substrate as a cathode and performing electroplating at a constant potential, wherein the electrodeposition potential ranges from -3.0 to 3.0 V, the deposition temperature is 30 to 80° C., and the deposition time ranges from 0.1 to 50 min during the electroplating process.

8. The method for preparing the Fe-Co-Ni-Cu-Zn high entropy sensing material according to claim 7, characterized in that: The conductive substrate includes but is not limited to titanium, copper, and silver; the electrode rod includes but is not limited to stone mill rod, lead, titanium, and platinum.

9. The method for preparing the Fe-Co-Ni-Cu-Zn high entropy sensing material according to claim 8, characterized in that: The conductive substrate also includes a pretreatment step before use, which includes first polishing the conductive substrate with sandpaper, then ultrasonically treating it for 5-20 minutes, then soaking it in a 0.5-2 mol / L sulfuric acid solution for 0.5-8 hours, then washing it with pure water and ethanol in turn, and drying it.

10. The method for preparing the Fe-Co-Ni-Cu-Zn high entropy sensing material according to claim 1, characterized in that: The proportion of each metal element in the Fe-Co-Ni-Cu-Zn high entropy sensing material is between 1% and 50%.

11. A Fe-Co-Ni-Cu-Zn high entropy sensing material, characterized in that: The material is prepared by the preparation method of the Fe-Co-Ni-Cu-Zn high entropy sensing material according to any one of claims 1 to 10.

12. A sensing electrode, characterized in that: Includes the Fe-Co-Ni-Cu-Zn high entropy sensing material as described in claim 11.

13. Use of the sensing electrode according to claim 12 in detecting the concentrations of urea and glucose.

14. Use of the sensing electrode according to claim 12 in detecting urea or glucose concentration, characterized in that: The detection concentration range of the urea is 0.2-1.4 mM, and the detection concentration range of the glucose is 0.1-0.5 mM.

Citation Information

Cited By

  • High-entropy alloy fiber material with core-shell structure as well as preparation method and application of high-entropy alloy fiber material

    CN119615318A

  • A core-shell structured high-entropy alloy fiber material, its preparation method and application

    CN119615318B